Sexual Desire and Related Factors in Middle-Aged and Elderly Married Women: A Cross-Sectional Study in Iran - Tabatabaeichehr, Mahbubeh (Open Access Maced J Med Sci, 2018)
BACKGROUND: The sexual desire in the middle-aged and senior women is one of the factors affecting their quality of life and psychological well-being. AIM: The present study was aimed to assess the sexual desire and related factors among married women aged 50-70 years. MATERIALS AND METHODS: In this descriptive-analytical study, 210 married menopausal women aged 50-70 years were selected by cluster sampling method. Data were collected using a demographic profile questionnaire and Sexual Desire Inventory (SDI), and analysed by SPSS version 22 software using descriptive statistics and independent t-test, ANOVA and Pearson correlation coefficient tests. RESULTS: The mean age of women was 59.40 ± 5.93 years, and the mean sexual desire score was 22.66 ± 17.78 (out of 112). There was a significant relationship between sexual desire score and age, educational level, occupation of women and spouses, age of menopause, marital history, number of pregnancies and children, individual health and pain level (P < 0.001). The sexual desire score had a significant association with diabetes, hypertension, heart disease, high cholesterol, chronic pain, gastrointestinal problems, chronic ulcers, bladder and intestinal problems, joint and bone disorders, taking cardiac medications, antihypertensive, anticoagulant, insulin, cholesterol-lowering drugs (P < 0.001). CONCLUSION: The low sexual desire score and its reduction with age and the presence of various diseases and factors affecting sexual desire highlight the importance of diagnostic screening, family related educational planning and the role of health care providers in the health status of the older adults.